PENERAPAN ZABBIX DENGAN NOTIFIKASI TELEGRAM UNTUK MELAKUKAN MONITORING JARINGAN - Heti, Heti; Khairil, Khairil; Lianda, Deri (Jurnal Media Infotama, 2024)
Urrently, The Use Of Computer Networks Is Very Necessary, Such As For Teaching And Learning Activities And Work. state high school 1 Kota Bengkulu Already Has A Network That Is Used For Teaching And Learning Activities. Currently The Computer Network In The Computer Laboratory Of state high school 1 Bengkulu City Totals 24 Computer Units.The Computer Network In The state high school1 Bengkulu City Computer Laboratory Does Not Yet Have A System That Can Carry Out Monitoring, So It Is Slow To Identify Problems That Occur On The Network. One Application That Monitors Networks Is Zabbix. Zabbix, In Monitoring The Network, Can Send Notifications To Telegram.Zabbix Can Run On The Linux Ubuntu Server 20.04 Operating System. The Linux Ubuntu Server 20.04 Operating System Is Used Because It Is Open Source And Does Not Require High Hardware Specifications. Because The Linux Ubuntu Server Operating System In Carrying Out Network Monitoring Using Zabbix Uses Small Server Resources. Zabbix Can Monitor Problems That Occur With Each Client And The Time When The Problem Occurs. Zabbix Can Also Send Problem Information In Real Time To The Network Admin's Telegram, So That Admins Can Easily Find Out About Problems That Occur On Computers Connected To The Network. Besides The Problem Information Sent To Telegram, It Is Also Saved In The Server Log, So That The Admin Can See The Problems That Occur At A Later Date